STUDI TINGKAT KERENTANAN PERMUKIMAN TERHADAP ABRASI PANTAI DI KELURAHAN BUNGUS SELATAN KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Manik, Denliati - (STKIP PGRI Sumbar, 2014)
This study aims to analyze the distance , slope, rock type , the average wave height , type ofbeach , condition of the building and determine the level of vulnerability of the population settlementsagainst coastal erosion in the Village of South Bungus Bungus Bay District of the city of Padang .Themethod used in this research is descriptive quantitative method. The sampling method with purposivesampling which appointment directly in the field sampling. The sample set of 15 sample pointssettlements located in coastal areas. Based on the results of the study showed that : the vulnerability ofthe population to abrasion settlements in the Village South at the fifteenth Bungus sample points are,there is one point of the sample is not vulnerable, 6 sample points are quite vulnerable, and 8 samplepoints settlements are vulnerable to deration.